2020
DOI: 10.1103/physrevresearch.2.013203
|View full text |Cite
|
Sign up to set email alerts
|

Levitons in helical liquids with Rashba spin-orbit coupling probed by a superconducting contact

Abstract: We consider transport properties of a single edge of a two-dimensional topological insulators, in presence of Rashba spin-orbit coupling, driven by two external time-dependent voltages and connected to a thin superconductor. We focus on the case of a train of Lorentzian-shaped pulses, which are known to generate coherent single-electron excitations in two-dimensional electron gas, and prove that they are minimal excitations for charge transport also in helical edge states, even in the presence of spin-orbit in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 114 publications
0
8
0
Order By: Relevance
“…Then, it is clear that in the presence of mixing and if channels propagate with different velocities v 1 = v 2 , it is not possible to synchronize all arrival times at the QPC and this results in a never vanishing noise. Clearly, the amount by which the HOM dip is reduced depends both on the difference in the time delays (51), but also on the mixing strength that modifies the relative weight of the three terms in Eq. ( 50).…”
Section: A Single Mixing Pointmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, it is clear that in the presence of mixing and if channels propagate with different velocities v 1 = v 2 , it is not possible to synchronize all arrival times at the QPC and this results in a never vanishing noise. Clearly, the amount by which the HOM dip is reduced depends both on the difference in the time delays (51), but also on the mixing strength that modifies the relative weight of the three terms in Eq. ( 50).…”
Section: A Single Mixing Pointmentioning
confidence: 99%
“…Several theoretical works [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] have investigated various properties of single-electron sources in this regime, and many experimental results [27][28][29][30][31][32][33][34][35][36][37][38] have shown that a high degree of control in the manipulation of single-electron excitations can be achieved. Moreover, extensions to interacting systems [39][40][41][42][43][44][45][46][47][48][49][50][51] have also been considered. In particular, the fractional quantum Hall regime plays a special role, due to the presence of fractionally charged quasiparticles, whose anyonic statistics can in principle be probed by electron quantum optics setups.…”
Section: Introductionmentioning
confidence: 99%
“…A specific and promising property of the systems just mentioned is that the strong SOC allows for the manipulation of a Rashba-like contribution [27][28][29][30] . To this end, external electric fields, induced for example by properly patterned side or top gates, can be used.…”
Section: Introductionmentioning
confidence: 99%
“…Even though the majority of EQO experiments have been performed on integer quantum Hall systems [2], proposals aiming at extending the domain of EQO to other settings have been put forward. They include the fractional quantum Hall regime [28,29], where experimental efforts are in progress [49], superconducting systems [50,51], and 2DTIs [52][53][54][55][56][57][58][59][60], a context in which the recent implementation of quantum point contacts [61] is very promising for achieving interferometric setups.…”
Section: Introductionmentioning
confidence: 99%